Lesson Study Mata Kuliah Telaah Kurikulum Buku Teks Fisika Untuk Meningkatkan Keterampilan Kolaborasi Mahasiswa Menggunakan Alur Merdeka - Yaspin Yolanda; Endang Lovisia (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2023)
This research is motivated by the low achievement of student competency skills in collaborating, student activities in collaborating only when discussing material, have not shown solid cooperation in designing independent curriculum teaching modules. The purpose of this study was to improve student collaboration skills through Lesson Study using independent flow, combined with Project Based Learning (PjBL) so as to enhance 21st-century skills. The sample of this study used purposive sampling with 40 physics education students at PGRI Silampari University—a quantitative descriptive research method. Data collection uses observation sheets, documentation, and interview guidelines. In open class meetings 1, 2, and 3 there was an increase in student collaboration skills using independent flow from meeting 1 to meeting 3 with an N-gain of 0.81 so the research results were in the high category.